WeChat as infrastructure: the techno-nationalist shaping of Chinese digital platforms. Issue 3 (3rd July 2019) - Plantin, Jean-Christophe; de Seta, Gabriele
Abstract : In the current research on media and communication, Western internet companies (e.g. Google and Facebook) are typically described as digital platforms, yet these actors increasingly rely on infrastructural properties to expand and maintain their market power. Through the case study of the Chinese social media application, WeChat, we argue that WeChat is an example of a non-Western digital media service that owes its success first to its platformization and then to the infrastructuralization of its platform model. Moreover, our findings show that the infrastructuralization of the WeChat platform model in China is shaped by markedly techno-nationalist media regulations and an increasingly overt cyber-sovereignty agenda. Drawing on the results of the analysis of technical documentation, business reports, as well as observations and interviews, we first present WeChat as both a platform and an infrastructure, and then we contextualize WeChat in the history of ICT infrastructure and the development of the internet in China. Finally, we analyze the specific role of the WeChat Pay service in establishing a new monetary transaction standard. We conclude by inquiring whether this emerging techno-nationalist model could be a plausible platform regulation in the future.